2014
DOI: 10.1111/are.12476
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate utilization by herbivorous and omnivorous freshwater fish species: a comparative study on gibel carp (Carassius auratus gibelio. var CAS III) and grass carp (Ctenopharyngodon idellus)

Abstract: Two 8-week feeding trials were conducted to evaluate dietary carbohydrate utilization by omnivorous gibel carp (Carassius auratus gibelio) (2.4 AE 0.1 g) and herbivorous grass carp (Ctenopharyngodon idellus) (6.5 AE 0.1 g). Five isonitrogenous (370 g kg À1 ) and isolipid (70 g kg À1) diets were formulated with increasing corn starch levels (60, 140, 220, 300 and 380 g kg À1 ). Resultsshowed that specific growth rate (SGR), feed efficiency (FE) and protein retention efficiency (PRE) of gibel carp significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 46 publications
6
37
2
Order By: Relevance
“…The present study found that the inclusion of digestible carbohydrate increased feeding rate (30C and 45C diet), but failed to improve fish growth. It is different with previous report that higher SGR of gibel carp was found in 30% corn starch diet when carbohydrate supplement from 6% to 38% (Li et al, 2016); this may associate with formulation of diets, especially for the fish meal content, and also with the difference in fish size. High carbohydrate diet showed presently protein-sparing effect of digestible carbohydrates by higher FE and PRE of 45C diet in accordance with previous reports (Kaushik, Medale, Fauconneau, & Blanc, 1989;Kim & Kaushik, 1992;Wilson, 1994).…”
Section: Gibel Carp Showed Well Utilization On Dietary Carbohydratecontrasting
confidence: 99%
“…The present study found that the inclusion of digestible carbohydrate increased feeding rate (30C and 45C diet), but failed to improve fish growth. It is different with previous report that higher SGR of gibel carp was found in 30% corn starch diet when carbohydrate supplement from 6% to 38% (Li et al, 2016); this may associate with formulation of diets, especially for the fish meal content, and also with the difference in fish size. High carbohydrate diet showed presently protein-sparing effect of digestible carbohydrates by higher FE and PRE of 45C diet in accordance with previous reports (Kaushik, Medale, Fauconneau, & Blanc, 1989;Kim & Kaushik, 1992;Wilson, 1994).…”
Section: Gibel Carp Showed Well Utilization On Dietary Carbohydratecontrasting
confidence: 99%
“…Digestive enzyme activities were determined by a series of factors, such as food, gene and nutritional habits (Zhang et al, 2010). Amylase activity could be induced by appropriate dietary carbohydrate level (Li et al, 2014); however, it was not found further increased but decreased when dietary carbohydrate level was higher than 45.31%, which indicated that excess carbohydrate level could inhibit amylase activity. Moreover, some researchers thought that there was no relationship between amylase activity and dietary carbohydrate level, and it was determined by genome and development (Drewe et al, 2004;German et al, 2004).…”
Section: Discussionmentioning
confidence: 83%
“…Fish, especially carnivorous fish, tend to be poor users of dietary carbohydrates (NRC, ). Diets for herbivorous and omnivorous fish species can be formulated containing 300–500 g/kg of carbohydrates (Boonanuntanasarn, Jangprai, et al, ; Li et al, ; NRC, ). However, for carnivorous species such as yellowtail kingfish ( Seriola lalandi ), largemouth bass ( Micropterus salmoides ) and Chinese longsnout catfish ( Leiocassis longirostris ), the amount of carbohydrates included in diets is generally <200 g/kg (Booth, Moses, & Allan, ; Liu et al, ; Tan, Xie, Zhu, Lei, & Yang, ).…”
Section: Introductionmentioning
confidence: 99%